Pretreatment out-of-pocket costs for people with drug-resistant tuberculosis in Bandung, Indonesia - Bony Wiem Lestari; Silvi Indriani; Adriana Viola Miranda; Dyah Ayu Nur Safira; Nur Ayu Fitriani; Raden Desy Nurhayati; Mirza Purwitasari; Almira Alifia; Alamanda Larasmanah; Iceu Dimas Kulsum; Arto Yuwono Soeroto (PLoS ONE, 2026)
Background People with drug-resistant tuberculosis (DR-TB) experience multiple visits to healthcare providers before DR-TB diagnosis and treatment. Our study aimed to quantify pretreatment direct costs and factors associated with higher costs among people with DR-TB. Methods Our cross-sectional study aimed to recruit 300 adults with pulmonary DR-TB from three DR-TB referral centers in Bandung, Indonesia, between February 2023 and February 2024. Participants were interviewed using a structured questionnaire regarding their demographic characteristics and out-of-pocket costs for the following categories: administration, chest radiography, laboratory tests, medication, travel, food, and other non-medical costs. Pretreatment out-of-pocket costs were analyzed descriptively, and factors influencing higher costs were examined using quantile regression. Costs were presented in U.S. dollars (USD, $) and reported as medians and interquartile ranges (IQRs). Results Among 258 eligible participants, 57.4% were male; median age was 38 years (IQR 27–47.7). A higher proportion of patients resided in rural areas (68.6%) and had initial visits to community health center (CHC) for TB-related symptoms (53.1%). The median pretreatment direct costs (excluding hospitalization) per person were estimated at $44.6 (IQR 18.8–92.7). The major contributors of pretreatment costs per person included hospitalization ($67.3), travel expenses ($13.7), chest radiography ($11.2), and medication ($10.8). Factors associated with greater pretreatment costs were residing in a rural area [β = 17.9, (95% CI: 1.07, 34.93)], had ≥ 7 visits to a healthcare provider [β = 19.9, (95% CI: 3.12, 36.74)], and their first TB symptom-related visit was to a private hospital [β = 38.7, (95% CI: 8.20, 69.30)], public hospital [β = 35.7, (95% CI: 8.60, 62.77)] and private primary care [β = 37.9, (95% CI: 19.36, 56.54)], compared to a community health center. Conclusions People with DR-TB in Indonesia incurred incremental direct costs during the pretreatment phase. Strengthening TB diagnostic infrastructure and sample referral networks between public and private providers in rural areas is critical to reducing the extra visits and financial burden for DR-TB patients.